Engineering Extracellular Vesicles with the Tools of Enzyme Prodrug Therapy. Issue 15 (23rd February 2018) - Fuhrmann, Gregor; Chandrawati, Rona; Parmar, Paresh A.; Keane, Timothy J.; Maynard, Stephanie A.; Bertazzo, Sergio; Stevens, Molly M.
Abstract: Extracellular vesicles (EVs) have recently gained significant attention as important mediators of intercellular communication, potential drug carriers, and disease biomarkers. These natural cell‐derived nanoparticles are postulated to be biocompatible, stable under physiological conditions, and to show reduced immunogenicity as compared to other synthetic nanoparticles. Although initial clinical trials are ongoing, the use of EVs for therapeutic applications may be limited due to undesired off‐target activity and potential "dilution effects" upon systemic administration which may affect their ability to reach their target tissues. To fully exploit their therapeutic potential, EVs are embedded into implantable biomaterials designed to achieve local delivery of therapeutics taking advantage of enzyme prodrug therapy (EPT). In this first application of EVs for an EPT approach, EVs are used as smart carriers for stabilizing enzymes in a hydrogel for local controlled conversion of benign prodrugs to active antiinflammatory compounds. It is shown that the natural EVs' antiinflammatory potential is comparable or superior to synthetic carriers, in particular upon repeated long‐term incubations and in different macrophage models of inflammation. Moreover, density‐dependent color scanning electron microscopy imaging of EVs in a hydrogel is presented herein, an impactful tool for further understanding EVs in biological settings. Abstract : Extracellular vesicles (EVs) are exploited as drug delivery vehicles but their therapeutic use may be limited due to off‐target effects. To harness EVs' inherent properties and to couple them with site‐specific drug delivery functions, EVs are incorporated into hydrogels and engineered with the tools of enzyme prodrug therapy. Local sustained release of antiinflammatory drugs is demonstrated in macrophage cell models.